UJI DAYA TERIMA PADA JELLY DRINK KENIKIR (Cosmos caudatus Kunth.) - Lina Muflihatul Hamidah; Wiwik Afridah; Endah Budi Permana Putri (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2018)
Kenikir (Cosmos caudatus Kunt.) has high antioxidants level. Kenikir jelly drink is selected as a fungsional beverage and with natural antioxidants. This research aims determine to the test received power of kenikir jelly drink and to know the antioxidant activity and nutritional content of panelist's favorite kenikir jelly drink. The research design is experimental with completed randomize nested one factor namely kenikir. The research population is kenikir jelly drink with sample of kenikir concentration is 0% (control) and 5%,10%, 15%. The research instrument consists of 30 trained panelists and closed questionnaires. The analysis used is descriptive statistics, One Way Anove, then continued by Duncan Multiple Range Test, α = 0,05. The result of this research shows that 5% kenikir jelly drink has high received power (69,17%) by panelist. Based on Anova test, the p-value is 0,00 which means that there is a difference of each treatment based on organoleptic test of color, taste, odor and texture parameters. Furthermore, the panelists favored sample were analyzed for the antioxidant and nutritional content. The result of this research shows that kenikir jelly drink 5% has high acceptance level with antioxidant activity of 86,61%, 83,13% of water content 0,20% of ash, 16,77% of carbohydrate, 0,53% of crude fiber and 67,08 Kcal.of energy. The suggestion of this research is the analysis of physical properties need to be held to know the food endurance of kenikir jelly drink.